3D-printed ternary SiO2CaOP2O5 bioglass-ceramic scaffolds with tunable compositions and properties for bone regeneration. Issue 8 (1st June 2019) - Li, Lei; Hu, Hongxing; Zhu, Yufang; Zhu, Min; Liu, Zhongtang
Abstract: Simple ternary SiO2 CaOP2 O5 bioglasses proved sufficient osteogenesis capacity. In this study, the bioglasses were 3D printed into porous scaffolds and SiO2 /CaO molar ratio was altered (from 90/5 to 60/35) to achieve tunable glass-ceramic compositions after thermal treatment. Scaffolds possessed interconnected porous structure with controllable porosities via 3D printing technique. In addition, microstructure and properties of mechanical strength, degradation, ion dissolution and apatite formation were investigated. Characterization results showed that higher content of SiO2 produced more homogeneous crystalline particles and sintering compactness, thus led to higher strength. For scaffolds with higher CaO content, more glasses were maintained and faster degradation rate including rapid ion release. In vitro human bone marrow mesenchymal stem cells were seeded on scaffolds, and the initial cell adhesion indicated good biocompatibility regardless of scaffold composition. Cell viability assays and osteogenic gene expressions showed proper SiO2 /CaO ratio played pivotal role to induce bone growth.